CMOS quadrature voltage-controlled oscillators and generators for wideband and multi-band transceivers - Xie, Juan (2011)
This thesis aims to provide a comprehensive study on the topic of CMOS quadrature voltage controlled oscillators and generators for wideband and multi-band transceivers, which pertains to the investigation, analysis, and design of different quadrature oscillators and generators. The quadrature oscillators and generators play important roles in the modern direct-conversion and low-IF transceivers. Various methods for generating quadrature signals have been explored. One way to produce quadrature signals is to use the RC polyphase network. The transfer functions of the 1st-, 2nd- and 3rd-order RC polyphase networks used for quadrature signal generation have been re-derived based on very basic principles. The new approach removed the need for the complex phasor and matrix analysis; and it was simple and comprehensive. The output signals’ matching behavior has also been explored. A quadrature generator consisting of a Voltage Controlled Oscillator (VCO), a 2nd-order RC polyphase network and output buffers has been designed and fabricated. In the presence of 15% component variation, it still achieved less than 0.5dB mismatch in amplitude and much less than 0.5º phase error. The quadrature generator had a frequency tuning range from 2.18GHz to 2.48GHz and it consumed 3.9mA current. Quadrature signals can be produced by cross-coupling two VCOs as well. The operation principle of the Series Quadrature VCO (Series QVCO) has been presented based on circuit analysis. It has been shown that by putting the coupling transistors in series with switching transistors, the quadrature signals could be generated intrinsically. A low power Series QVCO has been designed and fabricated.